RxBox 1.0 Beta live data telemetry, restructuring and FSM integration - Bangoy, Mark Jan C. (2011)
Telemedicine is the application of information and communications technology (ICT) in providing medical healthcare services and facilitating health information exchange between two or more remote locations. It involves biomedical signal acquisition, medical diagnosis, emergency care, immediate treatment, storage of patient's medical history and medical telemetry. Rural and several urban areas in the country have limited or no access to quality healthcare services. Quality healthcare is further hindered by the archipelagic nature of the country and the continuous migration of healthcare professionals. To address this problem, the Philippine Council for Health and Research Development (PCHRD) instituted the National Telehealth Service Program (NTSP). Rxbox, a component of the NTSP, is a Linux-based telemedicine appliance used to gather biomedical signals from patients and send them remotely to a central office. Now on its final phase, aptly named RXBox 1.0 Beta, the project enabled live biomedical data telemetry with the Triage, the central office in the Philippine General Hospital. Also, it was able to completely port the entire biomedical module application programming interface (API) to Linux. The project increased the Quality of Service (QoS) of the Rxbox units by providing system tests that aids healthcare personel in assessing the current status of the biomedical modules. Calibration procedures were also included to improve the accuracy of biomedical readings. Rxbox 1.0 Beta successfully migrated the software from an Asus EEE Top to an X50 shuttle. Also, with the new host computer, the project included the redesigning of the previous packagingto incorporate a new form factor. Better stability and faster development was achieved with the integration of system architecture. The architecture consists of the Finite State Machine Model which provided system predictability, Model-View-Control which enabled modularity and Pipe and Filter design which allowed 3rd party software integration.